Developing Virtual Web as Learning Media for Web Programming in SMK - Sorongan, Dedi; Mose, Yuliana; Berikang, Reonaldy A (JR Education, 2022)
The purposes of this research are (1) to generate virtual web as learning media subject specifically for web programming, (2) to find out the appropriateness of the product developed as a learning medium, and (3) to determine the effectiveness of the use of the e-learning for web programming subject. This research was through three stages: (1) the initial product development refers to the steps developed by Ivers& Barron namely Decide, Design, Develop, and Evaluate, (2) the testing ofthe product refers to the design of the test developed by Alessi&Trollip namely alpha testing, beta testing, and validating, and (3) the test ofthe effectiveness of using virtual web for the subjects of web programming by comparing the gain of pretest / posttest experiment group at XA TKJ class that uses virtual web, and the control class XB TKJ who do not use virtual web. Technical data analysis to the eksperiment product (test) using descriptive statistical in the form of statement very good, good, less good, less, much less which is converted in to quantitatif data at scale 5. The average result assesment categorizing ussing the assesment criteria by Widoyoko.The result of this research is a e-learning which is used speciallyfor web programming subject.The results of alpha testing phase, beta testing and summative test show that the e-learning is in the category of